2018
DOI: 10.1038/s41556-018-0093-4
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of H3K9me3-dependent heterochromatin during mammalian embryo development

Abstract: H3K9me3-dependent heterochromatin is a major barrier of cell fate changes that must be reprogrammed after fertilization. However, the molecular details of these events are lacking in early embryos. Here, we map the genome-wide distribution of H3K9me3 modifications in mouse early embryos. We find that H3K9me3 exhibits distinct dynamic features in promoters and long terminal repeats (LTRs). Both parental genomes undergo large-scale H3K9me3 reestablishment after fertilization, and the imbalance in parental H3K9me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
334
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(356 citation statements)
references
References 57 publications
19
334
3
Order By: Relevance
“…Additionally, this trend was markedly different to the expression dynamics of the other groups of genes analysed, which included genes coding for chromatin proteins, in general, DNA‐binding proteins, as well as the complete nucleome (Fig A). Thus, it is likely that constitutive heterochromatin is largely remodelled after fertilisation, fitting with the known dynamics of heterochromatin markers by immunostaining and of H3K9me3 ChIPseq . Interestingly, the timing of this increase also correlates with the reported increase in chromatin compaction between the 2‐cell and 8‐cell stages and the establishment of chromocentres from the late 2‐cell stage .…”
Section: Resultssupporting
confidence: 62%
“…Additionally, this trend was markedly different to the expression dynamics of the other groups of genes analysed, which included genes coding for chromatin proteins, in general, DNA‐binding proteins, as well as the complete nucleome (Fig A). Thus, it is likely that constitutive heterochromatin is largely remodelled after fertilisation, fitting with the known dynamics of heterochromatin markers by immunostaining and of H3K9me3 ChIPseq . Interestingly, the timing of this increase also correlates with the reported increase in chromatin compaction between the 2‐cell and 8‐cell stages and the establishment of chromocentres from the late 2‐cell stage .…”
Section: Resultssupporting
confidence: 62%
“…The loss of H3K9me3 enables lineage selection in early progenitor cells, accompanied by more dynamic changes than was thought previously 35 . Observations of early murine embryos, for example, have also shown that H3K9me3 may replace DNA methylation on TEs in a family-specific manner during preimplantation development 36 . H3K9me3 in the preimplantation epiblast, with its widespread DNA hypomethylation, might therefore 'mark' these TEs before DNA re-methylation occurs in the postimplantation epiblast.…”
Section: Tracing the Progression Of Hpgc-methylated Tes At The Onset mentioning
confidence: 99%
“…3b-c). To determine whether the inactive genes harbor histone marks associated with transcriptional repression, we integrated previously published H3K27me3 and H3K9me3 ChIP-seq datasets derived from oocytes and F1 hybrid embryos 17,40 . Consistent with a role for H3K9me3 in promoting DNAme maintenance, all 6 hypermethylated PDA loci are enriched for this histone PTM in oocytes ( Fig.…”
Section: Most Pda Target Genes Are Expressed During Spermatogenesis Amentioning
confidence: 99%
“…Indeed, while TET3-mediated oxidation followed by base excision repair has been implicated in this process, a TET-independent mechanism is also clearly involved [9][10][11][12][13][14][15] . Regardless, whole-genome bisulphite sequencing (WGBS) analyses reveal that DNAme levels on both parental genomes reach a low point in inner cell mass (ICM) cells of embryonic day 3.5 (E3.5) mouse blastocysts, followed by widespread de novo DNAme during post-implantation development [16][17][18] . This wave of genome-wide demethylation followed by remethylation is conserved in human embryonic development, albeit with slower kinetics [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%